2016
DOI: 10.3171/2015.4.peds14342
|View full text |Cite
|
Sign up to set email alerts
|

Differences in surgical outcomes for patients with craniosynostosis in the US: impact of socioeconomic variables and race

Abstract: OBJECT Craniosynostosis is often treated with neurosurgical intervention. The aim of this study was to report and analyze the clinical and socioeconomic characteristics of patients with craniosynostosis and to present current national trends. METHODS Using the Kids’ Inpatient Database for the years 2000, 2003, 2006, and 2009, the authors identified patients with craniosynostosis using International Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 24 publications
1
92
0
Order By: Relevance
“…19 Faris et al evaluated the impact of race on surgical outcomes of 3415 children surgically treated for craniosynostosis between 2000 and 2009 identified using the national Kids' Inpatient Database. 28 Similarly, they report that Caucasian patients were significantly younger at the time of surgery as compared with African American or Hispanic patients (6.1, 10.9, and 9.1 months, respectively; p < 0.0001).…”
Section: Discussionmentioning
confidence: 91%
“…19 Faris et al evaluated the impact of race on surgical outcomes of 3415 children surgically treated for craniosynostosis between 2000 and 2009 identified using the national Kids' Inpatient Database. 28 Similarly, they report that Caucasian patients were significantly younger at the time of surgery as compared with African American or Hispanic patients (6.1, 10.9, and 9.1 months, respectively; p < 0.0001).…”
Section: Discussionmentioning
confidence: 91%
“…Nonwhite race approached, but did not meet, a statistically significant association with increased patient scar selfconsciousness scores, which could suggest that the presence of a craniofacial deformity is likely a more foundational determinant of patient self-consciousness regardless of ethnic background. There are data that suggest that nonwhite patients are more likely to present in a delayed fashion for surgical care in comparison to their white counterparts (Shweikeh et al, 2016), but this effect was not reflected in our cohort. It is difficult to know to what extent aesthetic evaluations of scars are influenced by hair texture and length.…”
Section: Discussionmentioning
confidence: 62%
“…11 Therefore, it is now commonly believed that surgery should be performed as soon as possible, before the occurrence or exacerbation of clinical symptoms. 12 – 14 In addition, it has been demonstrated that surgery performed on symptom-free patients can prevent the development of late neurological deficits. 3 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…12 – 14 In addition, it has been demonstrated that surgery performed on symptom-free patients can prevent the development of late neurological deficits. 3 , 14 …”
Section: Discussionmentioning
confidence: 99%